Euthanasia from The Perspective of Normative Law And its Application in Indonesia - Agus Hermanto (Hunafa: Jurnal Studia Islamika, 2017)
There are differences of opinion among scholars regarding the issue of euthanasia. But the element of goodness makes a consideration, that preventing a disease is an obligation that must be done by every individual. While the difference is more depressed on how to apply euthanasia, namely on how to end the suffering of patients. In Islam, scientific and divine healing is known, while in medical science, only rational healing and emergency-based healing are known. In principle, the intentional killing of a sick person precedes fate. God has set the deadline for human life. By speeding up his death, the patient did not benefit from the test given by Allah to him.